Domestic water consumptions and associated factors in rural household of Harari region, Eastern Ethiopia; A cross sectional study - Ahmed, Bushra Yusuf; Tolera, Sina Temesgen; Temesgen, Liku Muche; Geremew, Abraham (Frontiers in Public Health, 2025)
BackgroundSustainable rural water supply management requires accurate estimations of water consumption and understanding factors influencing consumption. Climate change exacerbates challenges, especially in developing countries with high poverty and limited access to clean water. Ethiopia has the lowest municipal water supply in Africa. The residents of the Harar region currently get water once a week or two weeks for just a few hours, which is very inadequate for everyday household activities like drinking, cooking, cleaning utensils, washing clothes, etc. Despite global efforts to identify the factors that affect domestic water consumption, those related to domestic water use in rural regions have not been sufficiently studied, particularly in rural woredas of Harari region, Ethiopia.ObjectiveTo assess the domestic water consumption and associated factors at household level in rural woredas of Harari region, Eastern Ethiopia from October 29, 2022 to November 21, 2022.MethodA community-based cross-sectional study was conducted on 408 households using stratified sampling techniques, collecting data on socio-demographic and water use characteristics. Epi-Data and SPSS were used for data analysis. Descriptive analysis was used to determine average total and per capita water consumption, while a multiple linear regression model allowed for the identification of associated factors and the prediction of water consumption with statistical significance.ResultDaily water consumption was found to be 103.3 L/hh/d and 17.6 L/c/d. The associated factors included the main source of water, time of collection, household size, wealth status, water price, and frequency of gathering water.ConclusionThus, the provision of an adequate quantity of water for rural households should be given attention for maintaining human wellbeing, and the consideration of socio-economic factors affecting per capita water consumption is desirable in the planning and implementation of proper water demand management strategies.